2013
DOI: 10.1124/dmd.112.049817
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatic Disposition of Paroxetine Using Sandwich-Cultured Rat and Human Hepatocytes

Abstract: Paroxetine, a selective serotonin reuptake inhibitor, is metabolized in the liver and excreted into bile and urine as metabolites, but species differences have been observed in hepatic disposition between rats and humans. A major metabolite in rats is M1-glucuronide, whereas M1-glucuronide and M1-sulfate are found in humans. The primary excretion route of paroxetine-derived radioactivity in rats and humans is bile and urine, respectively. The aim of this study was to examine the usefulness of sandwich-cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…58 investigated the hepatic disposition of troglitazone using SCH and demonstrated biliary excretion of its sulfate and glucuronide. Matsunaga et al 59 evaluated hepatic disposition of paroxetine in rat and human SCH and showed well-preserved species differences in its hepatic disposition, which includes a series of metabolic steps followed by biliary excretion of metabolites in SCH. In addition, Tetsuka et al 61 investigated a series of events in glucuronidation and biliary excretion of mycophenolic acid (MPA).…”
Section: Application Of Sandwich-cultured Hepatocyte Models; Overall mentioning
confidence: 99%
“…58 investigated the hepatic disposition of troglitazone using SCH and demonstrated biliary excretion of its sulfate and glucuronide. Matsunaga et al 59 evaluated hepatic disposition of paroxetine in rat and human SCH and showed well-preserved species differences in its hepatic disposition, which includes a series of metabolic steps followed by biliary excretion of metabolites in SCH. In addition, Tetsuka et al 61 investigated a series of events in glucuronidation and biliary excretion of mycophenolic acid (MPA).…”
Section: Application Of Sandwich-cultured Hepatocyte Models; Overall mentioning
confidence: 99%
“…15,16) Moreover, there are some reports investigating in vitro biliary excretion of metabolites in addition to the parent compound in SCH. 17,18) Mycophenolic acid (MPA), an inosine 5A-monophosphate dehydrogenase inhibitor, is an immunosuppressive agent to prevent acute rejection in organ transplantation. MPA is frequently administered as a pro-drug (mycophenolic acid mofetil: MMF) that is rapidly converted to MPA in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most valuable applications of primary hepatocytes is to evaluate drug biliary excretion [4,50]. Here, we determined multiple transporter substrates' hepatobiliary disposition in the optimized iHep cells and compared that with primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%